2021
DOI: 10.1371/journal.pone.0246428
|View full text |Cite|
|
Sign up to set email alerts
|

Impacts of long-term inorganic and organic fertilization on phosphorus adsorption and desorption characteristics in red paddies in southern China

Abstract: Soil phosphorus (P) adsorption and desorption occur in an important endogenous cycle linked with soil fertility problems and relevant to the environmental risk assessment of P. In our study, the effect of long-term inorganic and organic fertilization on P adsorption and desorption characteristics in relation to changes in soil properties was evaluated by selecting three long-term experimental sites in southern China. The selected treatments at each site were CK (unfertilized), NPK (synthetic nitrogen, phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…However, the results obtained agree with the work of Berg and Joern, (2006), which showed a trend of increasing rather than decreasing sorption levels with increasing molecular mass of different forms of OP (IHP > G6P > ATP > IP). Similarly, recent work by Ganta et al, (2020) and Ahmed et al, (2021) also supported our results. They demonstrated that the organic fraction of the OP may not influence the interaction of individual phosphate groups with the soil and thus the effect of molecular mass steric hindrance may be insignificant.…”
Section: Influence Of Organic Phosphorus Properties On Adsorption And...supporting
confidence: 93%
See 1 more Smart Citation
“…However, the results obtained agree with the work of Berg and Joern, (2006), which showed a trend of increasing rather than decreasing sorption levels with increasing molecular mass of different forms of OP (IHP > G6P > ATP > IP). Similarly, recent work by Ganta et al, (2020) and Ahmed et al, (2021) also supported our results. They demonstrated that the organic fraction of the OP may not influence the interaction of individual phosphate groups with the soil and thus the effect of molecular mass steric hindrance may be insignificant.…”
Section: Influence Of Organic Phosphorus Properties On Adsorption And...supporting
confidence: 93%
“…were also used to determine the best-fitting isotherm to the experimental data. The conceptual framework was performed using correlate and network plot function in the latest development version of the corr package (Ahmed et al, 2021). This generates a network graph of a correlation data frame in which variables that are more highly correlated appear closer together and are connected by stronger paths.…”
Section: Discussionmentioning
confidence: 99%
“…Q m is considered an indicator of the capacity of soil to interact with phosphate, which to a certain extent governs soil P availability [ 18 ]. In this regard, previous studies have reported that long-term fertilization can modify the P adsorption capacity of soil [ 61 – 63 ]. In the present study, it was found that the fertilization of soil over the past four decades has had the effect of reducing the P adsorption capacity of soils in the research area, and we accordingly speculate that continuous application of fertilizers has contributed to a reduction in available exchange sites on the soil surface layer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the problem with artificial fertilization is that only 25-30 % of the P applied is available to crops, while the remainder is converted into insoluble P fractions (Penn and Camberato, 2019). Therefore different management strategies, including the use of efficient targeted P fertilizers, organic amendments, plants with low critical P-requirements, and modified farming systems, have been devised to increase P use efficiency in soil systems (Du et al, 2022;Qaswar et al, 2021;Ahmed et al, 2021;Simpson et al, 2011). However, there are limitations on how well these management strategies can improve P use efficiency.…”
Section: Introductionmentioning
confidence: 99%